Responses of ground-dwelling arthropods to long- term prescribed fire regimes in a savanna protected area. - Ludzula Mukwevho; Mduduzi Ndlovu; Gerald Chikowore; Tatenda Dalu; Reyard Mutamiswa; Frank Chidawanyika (Research Square, 2022)
Background Sound management of protected areas is crucial for biodiversity conservation. In savanna systems, fire is common, yet little is known on the direct and long-term effects of prescribed burns on arthropod abundance, richness, and diversity. Standardised pitfall traps and active searches were used to compare variation in abundance, richness and diversity of arthropods at various experimental burn plots in the Kruger National Park, a protected area in a savanna setting Results Hymenopterans: Formicidae were the most abundant (76.4%), whilst Coleopterans, Araneae and Orthopterans constituted 18.6, 3 and 1% of the total arthropods collected respectively. Coleopterans were the most diverse group (30.2%) compared to Hymenopterans: Formicidae (24.6), Araneae (24.6) and Orthopterans (4%). Abundance, species richness and diversity of multi-taxa significantly differed between the treatment plots. Abundance and diversity of Formicidae were signicantly lower, hence, species richness was significantly higher in annually burnt plots compared to the unburnt control plots. Although the highest number of arthropods was recorded in unburnt plots, species richness and diversity were lowest in these plots compared to those burnt annually and triennially. Conclusions We conclude that late summer burns do not have major ecological impact on arthropods, and it was demonstrated by the abundance and diversity of species recorded at the annually burnt plots. Thus, annual late summer burns can be used as a conservation tool for arthropod inhabiting the protected savanna of Kruger National Park.